Carbonated Hydroxyapatite Containing Propolis as an Antibacterial Agent Candidate against Aggregatibacter actinomycetemcomitans - Ayunda Nur Sukmawati; Sri Pramestri; Al. Sri Koes Soesilowati; Suryono Suryono (Majalah Obat Tradisional, 2020)
One of the periodontal pathogenic bacteria that can cause periodontitis and alveolar bone destruction is Aggregatibacter actinomycetemcomitans. An alveolar bone defect can be treated using a bone graft. Carbonated hydroxyapatite (CHA) is an alloplastic graft material. Alloplastic materials do not have vascularization, which will increase the risk of bacterial adhesion. Therefore, adding an antibacterial agent is needed to prevent bacterial adhesion, which will improve periodontal healing. Propolis is a natural ingredient that has broad-spectrum antibacterial activity and does not cause bacterial resistance. This study aimed to assess the antibacterial activity of carbonated hydroxyapatite after being incorporated with propolis against Aggregatibacter actinomycetemcomitans. Carbonated hydroxyapatite was embedded into four different concentrations of propolis solution (2.5%, 5%, 7.5%, and 10%). An antimicrobial assay against Aggregatibacter actinomycetemcomitans was done using the disc diffusion test method. The inhibition zone was measured to determine the antibacterial ability of the specimens. The inhibition zone was found on the carbonated hydroxyapatite incorporated with propolis at all concentrations. Carbonated hydroxyapatite incorporated with 10% propolis showed the largest inhibition zone. Data analysis using the Kruskal–Wallis test showed a significant difference between the groups tested (p <.05). In conclusion, carbonated hydroxyapatite incorporated with propolis has antibacterial activity against Aggregatibacter actinomycetemcomitans